1998
DOI: 10.1017/s0022112097007830
|View full text |Cite
|
Sign up to set email alerts
|

Observations of shock waves in cloud cavitation

Abstract: This paper describes an investigation o l the dynamics and acoustics of cloud cavitation, the structures which are often formed by the periodic breakup and collapse of a sheet or vortex cavity. This form of cavitation frequently causes severe noise and damage, though the precise mechanism responsible for the enhancement of these adverse effects is not fully understood. In this paper. we investigate the large impulsive surface pressures generated by this type of cavitation and correlate these with the images fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
120
0
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(131 citation statements)
references
References 27 publications
(60 reference statements)
10
120
0
1
Order By: Relevance
“…This lecture will review recent experimental and computational findings which confirm that, under certain conditions, the collapse of clouds of cavitating bubbles involves the formation of bubbly shock waves and that the focussing of these shock waves is responsible for enhanced noise and potential damage in cloud cavitation. The recent experiments of Reisman et al (1998) complements the work begun by Mørch and Kedrinskii and their co-workers and demonstrates that the very large impulsive pressures generated in bubbly cloud cavitation are caused by shock waves generated by the collapse mechanics of the bubbly cavitatting mixture. Two particular types of shocks were observed: large ubiquitous global pressure pulses caused by the separation and collapse of indiviual clouds from the downstream end of the cavitation and much more localized local pressure pulses which occur much more randomly within the bubbly cloud.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…This lecture will review recent experimental and computational findings which confirm that, under certain conditions, the collapse of clouds of cavitating bubbles involves the formation of bubbly shock waves and that the focussing of these shock waves is responsible for enhanced noise and potential damage in cloud cavitation. The recent experiments of Reisman et al (1998) complements the work begun by Mørch and Kedrinskii and their co-workers and demonstrates that the very large impulsive pressures generated in bubbly cloud cavitation are caused by shock waves generated by the collapse mechanics of the bubbly cavitatting mixture. Two particular types of shocks were observed: large ubiquitous global pressure pulses caused by the separation and collapse of indiviual clouds from the downstream end of the cavitation and much more localized local pressure pulses which occur much more randomly within the bubbly cloud.…”
supporting
confidence: 61%
“…A valuable first effort to do this was put forward by Kubota et al (1992) but by limiting the collapse of individual bubbles they prevented the formation of the large pressure pulses associated with bubble collapse. Wang et al (1994 and Reisman et al (1998) present accurate calculations of a simple spherical cloud subject to a low pressure episode and show that, for a large enough initial void fraction, the collapse occurs as a result of the formation of a shock wave on the surface of the cloud and the strengthening of this shock by geometric focussing as the shock propagates inward.…”
mentioning
confidence: 99%
“…The dissolved gas is the source of cavitation nuclei [14]. The dynamic load at the moment when cavitation bubble collapses lasts for a few microseconds Brought to you by | MIT Libraries Authenticated Download Date | 5/10/18 9:43 PM or nanoseconds [15]. Also the borehole environment is very favourable for formation of different types of corrosion outbreaks [7].…”
Section: Introductionmentioning
confidence: 99%
“…Pressure waves in the cavitating region are responsible for much of the unsteady features of cavitation. For example, the experiments of Reisman et al [1] showed that condensation shocks cause large pressure spikes which influence the behaviour of sheet cavities (e.g. [2,3]), and recent work has demonstrated that condensation shocks are responsible for the transition from stable to cloud-shedding cavities [4].…”
Section: Introductionmentioning
confidence: 99%